(untitled) (Baghdad Science Journal, 2020)
The presence of residual antibiotics in water results in the development of antibiotics resistant genes. The available wastewater treatment systems are not capable of removing such antibiotics from sewage. Thus, antibiotics need to be removed before the discharge of wastewater. Adsorption is among the promising techniques for the wastewater treatment to aid the removal of a wide range of organic and inorganic pollutants. The present work is a contribution to the search for an economical method for the removal of low concentrations of amoxicillin (AMX) from water by adsorption on water treatment residue, WTR, taken from a local drinking water facility. The chemical composition and the adsorptive characteristics of the material were first evaluated using energy dispersive spectroscopy, EDS, and sorption of methylene blue, respectively. The porous character of the sorbent was modified by ignition. The application of the WTR for the adsorption of AMX was studied under various operating conditions including sorbent dosage, 2-20 g/L at room temperature; contact time 30-240 min.; and initial concentration range of the antibiotic, 0.00004-0.00012 M. facility. To aid the experimental work, statistical software was employed to design the experiments and evaluation of the results. Graphical and mathematical relationships have been established for the adsorption efficiency with the operating conditions. The adsorption capacity was calculated from the plot of the adsorbed drug against the sorbent content and found to be 19.966 µmol/g WTR. The sorption efficiency depends on the initial concentration and being better at low concentration (0.00004 M) and equilibrium time (within 100 mins.). The optimum conditions of the adsorption are: AMX Concentration, 0.00004 M; Contact time. The optimum conditions of the adsorption are: AMX Concentration, 0.00004 M; Contact time, 90 min., and WTR content of 15.5 g/L to give removal efficiency of 89.2%.